Visualizing nanometric structures with sub-millimeter waves - Alonso Ingar Romero; Amlan kusum Mukherjee; Anuar Fernandez Olvera; Mario Méndez Aller; Sascha Preu (Nature Communications, 2021)
The authors demonstrate a far-field approach for height profile measurements with sub-millimetre waves. By evaluating Fabry-Pérot oscillations within surface-structured samples, combined with a Hilbert-transform approach, they visualize structures with a height of 49 nm, with 31 nm precision.